Peningkatan Kemampuan Pemecahan Masalah pada Materi Persamaan Garis Singgung Lingkaran melalui Pembelajaran Discovery Learning - Thasyia Indira; Zulkardi Zulkardi; Yanna Sanova (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
This study aimed to improve student’s problem-solving abilities of tangent circle equations using discovery learning. This research was done in class XI IPA 4 SMA N 1 Palembang. This research method is used Classroom Action Research with discovery learning models. The instrument is used test instrument in the form of an evaluating matter of the tangent circle equation in the description form and the observation sheet for observation of the learning activity of the students. The results of the study showed that there is an increase in students' problem-solving abilities in tangent circle equation material using discovery learning. This increase can be seen from the results of the post-test students with an average score of 93,6 which increased when compared with the results of the pre-test with an average value of 58,2. The percentage of students who complete learning increases from 30% pre-test to 100% at post-test with KKM (maximum mastery criteria) ≥ 70. Based on the data analysis, it can be concluded that learning with discovery learning models can improve student learning outcomes in the tangent of circle equation material.